Wellness and multiple sclerosis: The National MS Society establishes a Wellness Research Working Group and research priorities. (March 2018) - Motl, Robert W; Mowry, Ellen M; Ehde, Dawn M; LaRocca, Nicholas G; Smith, Kathy E; Costello, Kathleen; Shinto, Lynne; Ng, Alexander V; Sullivan, Amy B; Giesser, Barbara; McCully, Kevin K; Fernhall, Bo; et al.
Background: People with multiple sclerosis (MS) have identified "wellness" and associated behaviors as a high priority based on "social media listening" undertaken by the National MS Society (i.e. the Society). Objective: The Society recently convened a group that consisted of researchers with experience in MS and wellness-related research, Society staff members, and an individual with MS for developing recommendations regarding a wellness research agenda. Method: The members of the group engaged in focal reviews and discussions involving the state of science within three approaches for promoting wellness in MS, namely diet, exercise, and emotional wellness. Results: That process informed a group-mediated activity for developing and prioritizing research goals for wellness in MS. This served as a background for articulating the mission and objectives of the Society's Wellness Research Working Group. Conclusion: The primary mission of the Wellness Research Working Group is the provision of scientific evidence supporting the application of lifestyle, behavioral, and psychosocial approaches for promoting optimal health of mind, body, and spirit (i.e. wellness) in people with MS as well as managing the disease and its consequences.